[Au(η2‐C2H4)3]+[Al(ORF)4]– – a Stable Homoleptic (Ethene)gold Complex. Issue 15 (11th April 2013) - Schaefer, Julia; Himmel, Daniel; Krossing, Ingo
Abstract: The simple metathesis reaction of the silver(I) weakly coordinating anion (WCA) salt Ag[Al(OR F )4 ] R F = C(CF3 )3 with gold(I) chloride and ethene led to the formation of the second isolable tris(ethene)gold(I) complex, the last missing entry in the triad [M(C2 H4 )3 ] + [Al(OR F )4 ] – (M = Cu, Ag, Au). The Au atom is coordinated by three ethene ligands in a distorted trigonal‐planar manner in a so‐called spoke‐wheel arrangement. The formation of the tris(ethene) complex instead of the more expected bis(ethene) complex was analyzed by theoretical investigations and by a Born–Fajans–Haber cycle for [Au(C2 H4 )3 ] + [Al(OR F )4 ] – as well as the only other known example [Au(C2 H4 )3 ] + [SbF6 ] – . Abstract : The missing puzzle piece: [Au(η 2 ‐C2 H4 )3 ] + [AlOC(CF3 )3 4 ] – in a spoke‐wheel structure is the missing puzzle piece in the series of homoleptic univalent group 11 ethene complexes with the weakly coordinating anion [AlOC(CF3 )3 4 ] – . Herein, we describe the synthesis, characterization, and theoretical investigations of the second isolable, homoleptic η 2 ‐bound tris(ethene)gold(I) complex.